Untangling the Wallacean Shortfall: The herpetofauna of central-eastern Afghanistan including two snake species new for the reptiles list of the country - Jablonski, Daniel; Basit, Abdul; Randall, Patrick; Masroor, Rafaqat (Zootaxa, 2025)
Afghanistan’s herpetological diversity is not well studied due to limited access, environmental conditions, and historical socio-political instability. This study aims to address this gap by documenting the amphibians and reptiles found in central-eastern Afghanistan. Specifically, we focus on two new country records of colubrid snakes, Lycodon bicolor and Spalerosophis arenarius, presented in the study, provide updated provincial data on herpeto-diversity, and present an updated checklist of the family Colubridae for Afghanistan. The record of S. arenarius is further validated by sequences of two gene fragments of mitochondrial DNA, which also establish the phylogenetic context of the species within the genus. Our findings include records of four species of amphibians and 16 species of reptiles from the provinces of Kabul, Nangarhar, Paktia, and Wardak in central-eastern Afghanistan, representing two and nine families, respectively. In conclusion, this study highlights the potential for further significant herpetological discoveries in Afghanistan due to its biogeographic location between Central and South Asia. It also emphasizes the need for further systematic investigations using techniques of molecular taxonomy.